Mode Innovation and Discussion of Enterprise Financial Management in the New Economic Background (American Journal of Applied Statistics and Economics, 2024)
The development of the globalized economy has also made enterprise financial management work into a new stage of reform, the; transformation of the market economic system has also made the enterprise financial management work content and mode of change the traditional financial management model has failed to meet the needs of the current enterprise, and even hinder the development of enterprises. In the new economic background promoting financial management reform and innovation is not only the way of enterprise development. It is also in line with the trend of the times, where the article through the trend of economic development and in-depth analysis of the current financial management situation.By analyzing published literature and using the literature analysis method, we summarize the current problems in corporate financial management and propose corresponding solutions to the problems based on the key points of the problems, thereby providing reference and help for corporate development.